Producción audiovisual para la difusión de la escena musical independiente del género urbano de la Casa de la Cultura núcleo Tungurahua de la ciudad de Ambato - Navarro Morejon, Christian Daniel (2024)
This integrative project immerses itself in an in-depth investigation of urban music in the city of Ambato. By exploring this fascinating terrain, it reveals promising talent among young local artists, who, backed by their self-management and sharp creativity, have emerged as outstanding exponents of this genre in the locality. The research not only sheds light on the current state of urban music in Ambato, but also offers a journey through its evolution over time, covering both the contemporary scene and the musical legacy that has left an indelible mark on the urban community. In addition to the perspectives provided by the artists themselves, the project benefits from the contributions of professionals specialized in the relevant fields. These include audiovisual producers, urban musicians and, crucially, the voice of the consuming public. The research gives way to the essence of the project which focuses on the creation of high-quality audiovisual products, capturing the artistic character of independent urban musicians and serving as a powerful tool to disseminate their unique identity to young people and adults aged 17 to 40 in Ambato. Also, graphic pieces are incorporated which, when disseminated in digital media, amplify the visibility of these talented artists, establishing a synergy between the visual and the auditory. The careful combination of audiovisual and graphic elements not only amplifies the reach of these emerging artists, but also contributes to cultural enrichment and promotes musical diversity